PENGARUH INTEGRITAS, BEBAN KERJA, DAN TEKANAN ANGGARAN WAKTU AUDITOR TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI WILAYAH KOTA BEKASI DAN DKI JAKARTA) - Febriyani, Ratna Aulia; Maidani, Maidani; Eprianto, Idel (LPPM Institut Pendidikan Nusantara Global, 2024)
The purpose of this study was to find information and determine the effect of integrity, workload and auditor time budget pressure on audit quality. The data used in this study are primary data. The approach used is quantitative. The sample used in this study were auditors who worked at the Public Accounting Firm in Bekasi City and DKI Jakarta as many as 100 respondents. The sampling technique used in this study was purposive sampling. The data obtained is then processed with a data processing tool, namely the Statistical Program for Social Science (SPSS) Version 25. The conclusion from the results of this study is that integrity has a positive effect on audit quality, workload has no effect on audit quality and auditor time budget pressure has a positive effect on audit quality.